2018
DOI: 10.3390/w10020096
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Arsenic from Desalination Concentrate onto Drinking Water Treatment Solids: Operating Conditions and Kinetics

Abstract: Selective removal of arsenic from aqueous solutions with high salinity is required for safe disposal of the concentrate and protection of the environment. The use of drinking water treatment solids (DWTS) to remove arsenic from reverse osmosis (RO) concentrate was studied by batch sorption experiments. The impacts of solution chemistry, contact time, sorbent dosage, and arsenic concentration on sorption were investigated, and arsenic sorption kinetics and isotherms were modeled. The results indicated that DWTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Xu et al [98] applied batch sorption experiments to study the removal of As from aqueous solutions with high salinity. Drinking water treatment solids were used to remove As from reverse osmosis concentrates [98]. Each gm of solid derived from this treatment process is calculated to remove up to 170 mg of As [98].…”
Section: Removal Of As From Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Xu et al [98] applied batch sorption experiments to study the removal of As from aqueous solutions with high salinity. Drinking water treatment solids were used to remove As from reverse osmosis concentrates [98]. Each gm of solid derived from this treatment process is calculated to remove up to 170 mg of As [98].…”
Section: Removal Of As From Watermentioning
confidence: 99%
“…Drinking water treatment solids were used to remove As from reverse osmosis concentrates [98]. Each gm of solid derived from this treatment process is calculated to remove up to 170 mg of As [98]. Khan et al [99] optimized the As removal process using central composite design based on response surface methodology.…”
Section: Removal Of As From Watermentioning
confidence: 99%
“…Decreasing volatile NH 3 resulted in higher total N concentrations in poultry litter, thus resulting in a qualitative improvement in the waste production. Xu, Lin, Papelis, and Xu (2018) found that maximum sorption capacities of drinking water treatment solids to remove arsenic from reverse osmosis concentrate were 170 mg arsenic per gram of WTR.…”
Section: Introductionmentioning
confidence: 99%
“…Due to both their low cost and a relatively operational ease, there is now a raising interest on sorption methods that seem to be the most promising way to remove arsenic from water sources [11]. Several materials have already been studied for the adsorption of arsenic from water, including metal-loaded coral limestone [12,13] hematite and feldspar, sandy soils [14], activated carbon [15][16][17][18], activated alumina [19,20], lanthanum-impregnated silica gel [21], hydrous zirconium oxide [22] and hydrous iron oxide [23] and zero valent iron [24,25]. Ohki et al [13] found an adsorption capability of 150 µg/g As(V) on coral limestone, while Xu et al [14] investigated the adsorption capacity of drinking water treatment solids (DWTS) in As(V) removal processes: at its best, DWTS adsorption capability was found to be 170 mg/g, although heavily affected by pH conditions.…”
Section: Of 20mentioning
confidence: 99%